2012
DOI: 10.3844/ajassp.2012.388.391
|View full text |Cite
|
Sign up to set email alerts
|

Success in Business-A Brand Equity Perspective

Abstract: Problem statement:The study has been mainly attempted to find out the impact of the brand equity in overall success of the firm. The research has primarily been created to present a study on the significance of brand equity and its relevance in affecting the financial performance of the organization. Approach: The study has been conducted on the basis of secondary resources. The researches of different authors and theorists on the subject of brand equity and its relevance in affecting the financial performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Hypothesis 2 establishes a direct and positive relationship between brand equity and market value. The results have confirmed this relationship in both periods under study, which confirms what was previously concluded by authors such as Lo (2012) or Romero and Yagüe (2016) who also observed this relationship. In addition, in the case of this work, it should be noted that this relationship was verified for a type of companies with particular characteristics, such as multinational companies, without focusing on a specific sector.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hypothesis 2 establishes a direct and positive relationship between brand equity and market value. The results have confirmed this relationship in both periods under study, which confirms what was previously concluded by authors such as Lo (2012) or Romero and Yagüe (2016) who also observed this relationship. In addition, in the case of this work, it should be noted that this relationship was verified for a type of companies with particular characteristics, such as multinational companies, without focusing on a specific sector.…”
Section: Discussionsupporting
confidence: 92%
“…According to Lo (2012), it is accepted that brand equity has a significant contribution to increasing profitability and value for investors, which is directly related to the success of the organization.…”
Section: Brand Equity and Market Valuementioning
confidence: 99%
“…According to Lo (2012), it is widely accepted that brands significantly contribute to increasing profitability and shareholder value, which directly leads to business success. According to Madden et al (2006), firms that have developed strong brands create value for their shareholders by yielding returns that are greater in magnitude than a relevant market benchmark.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lo (2012) claimed brand may strengthen intangible assets and create overall success for companies. Loosley et al (2004) even claimed the brand itself possesses the concept of the copyright for legal perspective.…”
Section: Brand Equitymentioning
confidence: 99%